Cancer biologics made in plants. (February 2020) - Dent, Matthew; Matoba, Nobuyuki
Graphical abstract: Highlights: Plant overexpression systems facilitate preclinical biologics development. Plants have been used to produce many protein vaccines, mAbs, and immunotherapeutics. Plant virus nanoparticles are effective cancer-targeting agents. Plant-derived lectins and lectibodies may have unique anti-cancer potential. Abstract : Plants are routinely utilized as efficient production platforms for the development of anti-cancer biologics leading to novel anti-cancer vaccines, immunotherapies, and drug-delivery modalities. Various biosimilar/biobetter antibodies and immunogens based on tumor-associated antigens have been produced and optimized for plant expression. Plant virus nanoparticles, including those derived from cowpea mosaic virus or tobacco mosaic virus in particular have shown promise as immunotherapies stimulating tumor-associated immune cells and as drug carriers delivering conjugated chemotherapeutics effectively to tumors. Advancements have also been made toward the development of lectins that can selectively recognize cancer cells. The ease at which plant systems can be utilized for the production of these products presents an opportunity to further develop novel and exciting anti-cancer biologics.